Potential Health Impacts of Heavy Metal Concentrations in Fresh and Marine Water Fishes Consumed in Southeast, Nigeria - Agwu, K.K.; Okoye, C.M.I.; Okeji, M.C.; Clifford, E.O. (Pakistan Journal of Nutrition, 2018)
Background and Objective: Heavy metals refer to metallic chemical elements that have a relatively high density (4 g cm–3) that is greater than that of water. The presence or absence of some heavy metals is known to cause various diseases in humans. This study aimed to measure the concentrations of arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), lead (Pb), manganese (Mn), mercury (Hg), nickel (Ni) and zinc (Zn) in fish products consumed in Southeast Nigeria using an atomic absorption spectrophotometer (AAS). Methodology: The fish samples were purchased from local markets and included imported fish from marine water sources and fish from freshwater rivers and ponds. The samples were washed, de-scaled (where applicable) and oven-dried separately at 105°C for 10 h. A portion (2.0 g) of each of the dried homogenised samples was digested in a digestion flask with 20 mL of a mixture containing 650 mL of concentrated HNO3, 80 mL of perchloric acid (HClO4) and 20 mL of concentrated H2SO4. The heavy metal analysis was conducted using a Varian AA240 atomic absorption spectrophotometer. Results: The concentrations of the heavy metals between the freshwater and marine fish samples did not follow a regular pattern. All the fish products had mean heavy metal concentrations below the permissible limits. The highest concentrations of chromium and mercury were 114.377 and 3.718 mg kg–1, respectively. Mercury had a target hazard quotient>1.0. Conclusion: Consuming the sampled fish products has the potential to cause adverse health impacts if not controlled.